Effects of pure and ozonated sunflower seed oil (Helianthus annuus) on hypergranulation tissue formation, infection and healing of equine lower limb woun - Filippo, Paula Alessandra Di; Ribeiro, Luiza Maria Feitosa; Gobbi, Francielli Pereira; Lemos, Gabriela Bravim; Rodrigues, Rachel Bittencourt Ribeiro; Jerdy, Hassan; Silva, Larissa Carvalho Da; Viana, Inácio Silva [UNESP]; Quirino, Célia Raquel (Revista Brasileira de Medicina Veterinaria, 2020)
This study was undertaken to evaluate the therapeutic effects of topical application of pure sunflower seed oil (oil group) and ozonated sunflower seed oil (ozone group) on acute cutaneous wound healing in eight healthy horses. The control group was treated with 0.9% sodium chloride. Two wounds were surgically produced on each horse on the proximal epiphysis of the metacarpus on the dorsal aspect of each forelimb. Wound area and contraction were measured on days 0, 3, 7, 14 and 21. Biopsy samples were taken to evaluate epithelial hyperplasia, inflammation, exuberant granulation tissue, exudate type, angiogenesis, and fibroplasia. Culture swabs were also collected. Wound contraction at 21 days for the oil group was 52.68%, for the ozone group was 72.16%, and for the control group (0.9% sodium chloride) was 34.80%. The ozone group had a significantly smaller wound size and a residual wound area than the control and the oil groups, on days 14 and 21. The control-wounds and oil-wounds had suppurative exudate and the presence of Streptococcus zooepidemicus. Neutrophilic inflammatory infiltrate was observed in all groups. Granulation tissue was observed on day 7 in all groups, but exuberant granulation tissue was observed only in the control group on days 14 and 21. Reepithelialization was observed on day 14 in the ozone group. In conclusion, these results demonstrate that topical application of ozonated sunflower seed oil accelerates acute cutaneous wound repair in horses, preventing hypergranulation tissue and infection, and that it is superior to treatment with pure sunflower seed oil and 0.9% sodium chloride.
Keywords: Equine; Healing; Ozone; Phytotherapy; Wound